Analisis Dampak Covid-19 Pada Penataan dan Laba UMKM (Studi Kasus Pada : Stand Booth Drink Time Bandar Jaya): Indonesia - Rikita Sirait, Ribka Rikita Sirait (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
The UMKM Booth Stand in Bandar Jaya is currently estimated to be almost 50 booth stand actors who sell a variety of foods and drinks, this booth stand's stand alone using their own business capital, the booth stand engaged in the food and beverage business has been around since October 2017 until now. However, there are problems that occur from the covid-19 outbreak in 2019 to 2021, this study is to determine the difference in revenue and profit before and during covid-19. This research uses the Research Method used is a qualitative method, namely a method whose research data is collected from documents, records, and reports related to the problem to be solved at the same time. This research uses one informant located in Bandar Jaya. Data analysis techniques in this descriptive qualitative are carried out by searching and collecting data by researchers which are then arranged systematically through field notes or documentation. The process is as follows: 1) data reduction, 2) data presentation, 3) data verification of conclusions. Data validity techniques include 1) credibility, 2) data transferability, 3) data dependability, 4) data practicality. The results showed that the highest decline in Drink Time Booth revenue in the period 2019 to 2020 occurred in August with a percentage of -0.6%. Profit in 2019 to 2020 at Drink Time Booth Stand decreased in March with a percentage of 0.03% and followed in February with a percentage of 0.06%. In order not to experience bankruptcy Stand Booth Drink Time can make business capital loans to related parties.